Evaluation of the toxicity data for peracetic acid in deriving occupational exposure limits: A minireview. Issue 1 (17th February 2015) - Pechacek, Nathan; Osorio, Magdalena; Caudill, Jeff; Peterson, Bridget
Highlights A mini-review of the toxicity data for peracetic acid (PAA) was conducted in the context of deriving health-based occupational exposure limits (OEL). The available toxicity data for PAA frequently suffer from deficiencies in reporting, information gaps and unconventional testing methodology In spite of these limitations, sensory irritation is identified as the most sensitive health endpoint and serves as the point-of-departure upon which health-based OELs are derived. Time-weighted average (TWA) OELs are derived and range from 0.36 to 0.51 mg/m3 (0.1–0.2 ppm). Short-term exposure limit (STEL) OELs also are derived and range from 1.2 to 1.7 mg/m3 (0.4–0.5 ppm). A joint TWA/STEL approach is recommended to effectively mitigate PAA workplace inhalation hazards with selection of specific OELs within the proposed ranges being a risk management decision.